Coexisting Kondo hybridization and itinerant f-electron ferromagnetism in UGe_{2} - Ioannis Giannakis; Divyanshi Sar; Joel Friedman; Chang-Jong Kang; Marc Janoschek; Pinaki Das; Eric D. Bauer; Gabriel Kotliar; Pegor Aynajian (Physical Review Research, 2022)
Kondo hybridization in partially filled f-electron systems conveys a significant amount of electronic states sharply near the Fermi energy leading to various instabilities from superconductivity to exotic electronic orders. UGe_{2} is a 5f heavy fermion system, where the Kondo hybridization is interrupted by the formation of two ferromagnetic phases below a second order transition T_{c}∼52K and a crossover transition T_{x}∼32K. These two ferromagnetic phases are concomitantly related to a spin-triplet superconductivity that only emerges and persists inside the magnetically ordered phase at high pressure. The origin of the two ferromagnetic phases and how they form within a Kondo-lattice remain ambiguous. Using scanning tunneling microscopy and spectroscopy, we probe the spatial electronic states in the UGe_{2} as a function of temperature. We find a Kondo resonance and sharp 5f-electron states near the chemical potential that form at high temperatures above T_{c} in accordance with our density functionaltheory+Gutzwiller calculations. As temperature is lowered below T_{c}, the resonance narrows and eventually splits below T_{x} dumping itinerant f-electron spectral weight right at the Fermi energy. Our findings suggest a Stoner mechanism forming the highly polarized ferromagnetic phase below T_{x} that itself sets the stage for the emergence of unconventional superconductivity at high pressure.